Role of Glucose in the Expression of Cryptococcus neoformans Antiphagocytic Protein 1, App1 - Williams, Virginia (American Society for Microbiology, 2011)
The cryptococcus-specific protein antiphagocytic protein 1 (App1) regulates Cryptococcus neoformans virulence by controlling macrophage-driven fungal phagocytosis. This is accomplished through complement receptors (CR), specifically CR3. When inhaled, C. neoformans can cause a life-threatening meningoencephalitis in immunocompromised patients. Because glucose starvation can significantly change the gene expression and virulence of C. neoformans and because App1 is critical for phagocytosis in the lung—a low-glucose environment—we investigated the role of glucose in App1 expression. We found that App1 was upregulated dramatically under low-glucose conditions, and it was upregulated when C. neoformans cells were incubated in bronchoalveolar lavage (BAL) fluid, serum, and cerebrospinal fluid, which are low-glucose environments. Characterization of App1's regulation based on mammalian lung physiology revealed that App1 is upregulated via both increases in transcription and increases in mRNA stability. Our data provide new insights regarding C. neoformans adaptations to low-glucose environments.